Teachers’ Use of Code-Switching and Secondary School Students’ achievement in Oral English in Oyo West Local Government area, Oyo State - Olakunle, Araromi Maxwell (NIU Journal of Humanities, 2023)
This study investigated teachers’ use of code-switching and secondary students’ achievement in oral English in Oyo West Local Government Area, Oyo State. The descriptive survey research design of correlational type was adopted.  Five senior secondary schools were randomly selected from eleven (11) public senior secondary schools in Oyo West Local Government Area of Oyo State. A total number of two hundred (200) students and ten (10) teachers participated in the study. Teacher Code-Switching Observation Schedule (TCSOS) and Oral English Achievement Test (OEAT) were used to collect data. Data were analysed using the descriptive and inferential statistics.  The study showed the most important reason for teacher code- switching is that the teachers use code-switching to increase students’ participation during lessons. It was recommended that teachers should have knowledge of oracy skills so as to give quality knowledge to students in the area of oral English. Key w ords: Code-Switching, Secondary School Students, Achievement in Oral English, Teachers’ Use, Oyo West